(untitled) - Achtemeier, Paul J.; (1927-2013) (U.S.A, 1985)
More than 3,500 articles, written by members of the Society of Biblical Literature, present essential information on every aspect of the Old Testament, Apocrypha, and New Testament and are supplemented by photographs, maps, tables, and charts.
Keywords: Bible -- Dictionaries